2020
DOI: 10.17556/erziefd.643057
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of High School Students’ Attitudes towards the Use of Augmented Reality Applications in Biology Instruction

Abstract: This study aims to investigate the attitudes of students towards augmented reality applications. The study was designed with a mixed methodological approach where quantitative and qualitative methods were used together and carried out with 618 high school students from 10 different schools. For the collection of quantitative data, the Augmented Reality Applications Attitude Scale was used. In the qualitative data collection, a semi-structured interview form was prepared and applied to 18 students, two students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
4
0
3
Order By: Relevance
“…The positive attitude of AR technology toward the environment can be clarified by the fact that AR technology provides students with a positive attitude toward AR technology and offers an exciting learning experience. Many studies have shown that participants develop positive attitudes toward AR technology (Atalay & Akgün, 2020;Küçük et al, 2014). A positive attitude towards the practice may have affected a positive attitude toward the environment.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The positive attitude of AR technology toward the environment can be clarified by the fact that AR technology provides students with a positive attitude toward AR technology and offers an exciting learning experience. Many studies have shown that participants develop positive attitudes toward AR technology (Atalay & Akgün, 2020;Küçük et al, 2014). A positive attitude towards the practice may have affected a positive attitude toward the environment.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Bu bölümde, YÖK Ulusal Tez Merkezi'nde taranan lisansüstü tezlerin belirlenmesi, nitelik ve niceliğine göre değerlendirilmesi sonucunda; tezlerin türleri, üniversite dağılımı, enstitü türleri, program türleri, çalışmaların yıllara göre dağılımı, kullanılan yöntemler ve tezlerin konuları, tablo hâline getirilerek aşağıda sunulmuştur. Ak, 2018;Akkiren, 2019;Akkuş, 2016;Alagöz, 2020;Atalay, 2019;Ateş, 2018;Avcı, 2018;Azı, 2020;Babur, 2016;Başal, 2019;Coşkun, 2019;Çankaya, 2019;Çetin, 2019;Çınar, 2017;Demirel, 2017;Demirel, 2019;Erbaş, 2016;Fidan, 2018;Gül, 2016;Gün, 2014;Gündüz, 2020;Kara, 2018;Kul, 2019;Kurtoğlu, 2019;Kuzgun, 2019;Özdemir, 2017;Sırakaya, 2015;Sönmez, 2019;Sünger, 2019;Şahin, 2017;Şahin, 2019;Türksoy, 2019;Yıldırım, 2016;Yıldırım, 2018;Yıldırım, 2019;Yıldırım, 2020;Yılmaz, 2018) Materyal geliştirme / değerlendirme 2 4,35 (Küçük, 2015;Şentürk, 2018) Öğretmen / Akademisyen görüşleri 3 6,52 (Eroğlu, 2018;Kızılca, 2019 Babur, 2018;Gün, 2014;…”
Section: Bulgularunclassified
“…It is seen, more different variables for future research suggesting research on different learning groups are offered. Some studies like Altan (2019) suggests that research on different learning groups with different variables, while some studies where only experimental for example a study by Aydındoğan and Ürey (2021) suggests for future researchers to do in depth examination with studies and add methods in quantitative and qualitative methods, but most of the studies suggested that future researchers should do more studies to reduce the use of the, mobile augmented in health education while if we check the literature review of some studies you will notice that the study groups were short to primary and secondary education a study by Atalay and Akgün (2020) suggests that there should be more study groups but in different levels in schools and universities the study that been carried out by Akkiren (2019) mentioned in the literature review that the latest studies were permitted to the high school and primary but to certain levels it was suggested do more study at the primary and university level, however there were suggestions also to do more research in different geographical regions in the study by Aslan and Erdoğan (2017) and Ağaçayak (2019) while some other studies suggested to use updated tools especially the experimental studies for example: Ürey (2021) as well as Boyaci and Aslan (2020), augmented reality in health education and how the use of this technology it is to give the students the opportunity to learn anywhere anytime and also increased the leaning, and understanding in the students thanks to the easy-to-use technical methods that used to make it easier for the students to easily understand the instruction use of the applications which increasing the success rate and achievement, which also decrease the amount of time needed in training in health education the analysis of the data gathered in this study also show how the use of this technology is been developing through the years regardless of the number of the studies showing the level of the education is applied it shows the positive increase in the response and the use of the technology and the majority of the study has a positive results within the studies conducted on the subject, AR applications have a positive impact on academic success and hence based on the study by Batdı and Talan (2019) as earlier mentioned not only it has learning and performance gains and retention the memory it also helps improving the skills of solving problem and the progresses the degree of participation among students and among the reasons that increase the academic success in the students is the it can facilities the students to increase their motivation and the positive response toward the course and the technology most of the studies focus on higher education and the self-improvement that the students get while using the applications in AR is another major advantage that is been mentioned in the listed studies the combination between the real world and the virtual world gives the students to test their natural abilities and motivate them toward technology development.…”
Section: The Effect Of Findings On Health Educationmentioning
confidence: 99%